Ergogenic effect of acupuncture in sport and exercise: A brief review - Ahmedov, S. (The Journal of Strength and Conditioning Research, 2010)
Acupuncture is one of the most popular alternative methods applied in Western medical practice. In addition to its curative properties in various chronic conditions, demonstrated by the number of clinical trials, acupuncture has been recently applied as an enhancer of sports performance. Reviewed studies of published literature on the use of acupuncture in resistance and endurance sports activities demonstrated the association of traditional acupuncture protocol with increase of muscular strength and power. In cases regarding endurance activities, acupuncture treatment improved hemodynamic parameters of participants but not their aerobic performance. Further metodologically strong studies with inclusion of both biomedical and traditional Chinese theories are needed to assess the usefulness of acupuncture in enhancement of sports performance.